Efectos de la incubación artesanal de huevos de Chelonoidis denticulata (Linnaeus,1766) "motelo" en tres tipos de sustratos en el zoocriadero MF Tropical Fish, Loreto-Perú - Ramirez Coral, Liz Karelia (2022)
In order to determine the effect of three types of substrates on the incubation period and hatching success of Chelonoidis denticulata eggs, an experimental study was carried out from March to September 2018. 252 Chelonoidis denticulata eggs were collected from the MF TROPICAL FISH Zoo, located on the Iquitos-Nauta Highway, being distributed in 9 artisanal incubators, with three types of substrates AB (T1), TNE (T2) y AB + A (T3), with a density of 28 eggs/incubators. The temperature of the incubators was monitored daily, the incubation period was recorded and the hatching rate of the eggs was determined. Significant differences were recorded in the incubation period, being the T1 (x = 120.4 ± 1.22 days, min-max = 150-127 days) with the lowest period, followed by T2 (x = 168 ± 2.78 days; min-max = 155-179 days and T3 (x = 176.5 ± 3.27 days; min-max = 168-180 days). The highest hatching rate was recorded in T2 (82.14%) and the lowest in T1 (51.19%), with significant differences (p<0.05). The average temperature of the incubators was 28.25 °C (T1), 29.56 (T2) and 29.33 (T3), with significant differences (p<0.05) between the treatments. In conclusion, the use of the ruffled earth substrate (T2) in the incubation of Chelonoidis denticulata eggs helps to increase the percentage of hatching and survival of the neonates.